Social Value, Obstacle, and Learning Strategy in Implementing Mathematics Subject at the School Level - Wibowo, Rimun; Bahagia, Bahagia; Halim, Abdul Karim; Dwikorawati, Syarifah Sofiah; Saripuddin, Usep (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
Mathematics lessons are always considered a difficult subject although some think math is very fun. This study aims to find the social values ​​built from mathematics lessons, challenges, and teacher strategies to realize mathematics learning. The research method used is qualitative research methods. While the sampling was done by purposive technique, namely directly determining the respondents who were used as samples. Meanwhile, data was collected in three ways: in-depth interviews, documentation, literature search, and observation. The results of the study indicate that mathematics contains social values ​​because in completing mathematics lessons there is no escape from the value of working together, the value working together or helping each other, and social interaction when working on math problems. Even group-based mathematics lessons will foster group life among students. At the same time, there are other social values, such as when children are in a social environment, children want to shop, then math lessons are very helpful for children because children can calculate change, how much they have to pay, and cannot be lied to. Third, mathematics lessons are full of challenges because they depend on students, if students have a strong drive to learn, they will like mathematics. Of course, teachers have ways to overcome them, including teachers who learn first from youtube tutorials so that they can teach children so that lessons are not only understood by teachers but can also be understood by students.